The art of digital influence: leveraging SWOT analysis for VPC-based WOM at Street’s Fank’s - Raya Ramadhani Kasman; Imam Al Gazali; Ardhan Naf’an Amani; Ghinaa Nur Sharfina (Institute of Computer Science (IOCS), 2025)
Introduction: Digital transformation compels SMEs to translate physical authenticity into digital capital, yet inconsistencies often hinder this process. This study addresses the critical gap observed at Street's Fank's Coffee Shop, where strong, organic verbal Word-of-Mouth (WOM) fails to be leveraged effectively through Instagram Marketing. Objective: The research aims to analyze the disconnect between physical social capital and digital execution and proposes an integrated strategy to sustain digital WOM. Methods: Employing a qualitative descriptive approach, data were collected through triangulation: non-participant observation, in-depth interviews with key informants (Owner and Social Media Admin), and documentation in Samarinda Seberang. Data analysis followed open, axial, and selective coding procedures. Results: The study reveals a fundamental 'disconnect' where the shop's most valuable asset—abundant User Generated Content (UGC) derived from authentic physical experiences—is systematically neglected. This occurs because the management views content creation as a burden, leading to digital inconsistency despite the availability of organic customer endorsements. Conclusion: To overcome this, the study proposes